2019
DOI: 10.2147/cmar.s208818
|View full text |Cite
|
Sign up to set email alerts
|

<p>CDH1 (E-Cadherin) Mutation and Gastric Cancer: Genetics, Molecular Mechanisms and Guidelines for Management</p>

Abstract: IntroductionGermline mutation in CDH1 (E-cadherin) tumor suppressor gene is associated with hereditary diffuse gastric cancer (HDGC) and lobular breast cancers (LBC). E-Cadherin protein is necessary for physiological signaling pathways, such as cell proliferation, maintenance of cell adhesion, cell polarity and epithelial-mesenchymal transition. Dysregulation leads to tumor proliferation, invasion, migration and metastases. We review current perspectives in CDH1 genetics with molecular mechanisms and also disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 68 publications
(119 reference statements)
2
85
0
1
Order By: Relevance
“…In addition, a study reported two CTNNA1 variants (nonsense and frameshift) in 2 unrelated HDGC families both showed loss of -catenin protein expression and preserved E-cadherin expression. It is known that -catenin is a critical component of an adaptor protein complex to bridge E-cadherin and filaments of cytoskeleton, and maintains cell stability as well as inhibiting cell motility (7). Therefore, the variant in CTNNA1 detected in this study may hold the potential to impair normal function of E-cadherin-catenin complex and contribute to diffuse type pathology.…”
Section: Other Potential Deleterious Variants Identified In Candidatementioning
confidence: 79%
See 1 more Smart Citation
“…In addition, a study reported two CTNNA1 variants (nonsense and frameshift) in 2 unrelated HDGC families both showed loss of -catenin protein expression and preserved E-cadherin expression. It is known that -catenin is a critical component of an adaptor protein complex to bridge E-cadherin and filaments of cytoskeleton, and maintains cell stability as well as inhibiting cell motility (7). Therefore, the variant in CTNNA1 detected in this study may hold the potential to impair normal function of E-cadherin-catenin complex and contribute to diffuse type pathology.…”
Section: Other Potential Deleterious Variants Identified In Candidatementioning
confidence: 79%
“…The genomic length of CDH1 is approximately 100kb, and it is transcribed into 4.5-kb mRNA followed by being translated to a 120kDa E-cadherin, a highly conserved transmembrane glycoprotein whose function is to maintain calcium-dependent cell-cell adhesion through association of cytosolic protein complex mainly formed by catenins (6,7). Therefore, susceptibility for gastric cancer in CDH1 mutation carriers is suggested to be attributed to aberrant E-cadherin function or protein loss, since a normal functioning E-cadherin is highly required by various signalling pathways and cross talks to maintain the balance of cell proliferation, motility and polarity (7). In addition, the estimated cumulative risk for CDH1 mutation carriers to develop GC by age 80 years is 67% for men and 83% for women (8).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of function due to methylation or deletion of CDKN2A has been observed in many cancers [24]. Additionally, the importance of DAPK and CDH1 in cancer has been revealed [25,26]. Because these four genes play an important role in carcinogenesis, we could not exclude the possibility that methylation of these genes renders them silent, and hence, directly contributes to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand if we study the diffuse gastric cancer (usually hereditary), whose incidence is on the rising trend in the recent years in the younger population, it takes a small proportion of the total gastric cancers in the world but usually has fatal outcomes in these patients because of its aggressive nature of infiltrating the mucosal wall of the stomach known as linitis plastica. The outcomes are fatal because of their late presentation of symptoms in their course and by then the spread engulfs major organ systems of the body [4].…”
Section: Introductionmentioning
confidence: 99%